Energy Planning - Gielen, Dolf (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The world needs an accelerated energy transition to meet sustainable development goals. Energy planning has a critical role in providing the information that can guide decision-makers, and energy planning methods continue to evolve rapidly. This Special Issue provides new insights for long-term energy planning, drawing on the Clean Energy Ministerial Long Term Energy Planning Scenarios initiative and the IRENA LTES network.